The Relationship of Parental Income to Student Career Selection of Culinary Skills Program - Ibrahim An-Nakha'i AD; Elida; Kasmita; Lucy Fridayati (Siber Journal of Advanced Multidisciplinary, 2026)
Career selection is a strategic process for Vocational High School students because it relates to the direction of work, entrepreneurship, or continuing their studies after graduation. This study aims to (1) describe parental income, (2) analyze student career selection based on three main pathways, and (3) examine the relationship between parental income and student career selection of Culinary Skills Program. The research uses a quantitative approach with a correlational design. The population amounted to 202 students and a sample of 135 students was selected through proportional stratified random sampling. Parents' income is measured from the categories of basic income and additional income of fathers and mothers. Career selection was measured with 40 seven-level Likert scale statements. The trial on 30 respondents retained 40 valid points out of the initial 48 points and resulted in a Cronbach's Alpha of 0.947. The results showed that 76.3% of fathers and 87.4% of mothers were in the category of non-income or income below Rp2,500,000 per month; As many as 65.9% of fathers and 74.8% of mothers have no additional income. Overall career selection is most in the high category (44.4%). The entrepreneurial aspect obtained the highest respondent achievement rate of 69.35%, followed by 67.85% working and continuing studies 64.40%. The Spearman correlation yields r_s = 0.110 and p = 0.202, so the relationship between the two variables is positive, very weak, and insignificant. The square of the correlation coefficient of 1.22% indicates a very small joint association. The findings confirm that career services need to strengthen self-efficacy, information, practical experience, and non-financial support, not just consider family economic backgrounds.